Timing gamma-ray pulsars with the FERMI large area telescope: timing noise and astrometry - Kerr, M.; Ray, P.; Johnston, S.; Shannon, Ryan; Camilo, F. (2015)
We have constructed timing solutions for 81 γ-ray pulsars covering more than five years of Fermi data. The sample includes 37 radio-quiet or radio-faint pulsars which cannot be timed with other telescopes. These timing solutions and the corresponding pulse times of arrival are prerequisites for further study, e.g., phase-resolved spectroscopy or searches for mode switches. Many γ-ray pulsars are strongly affected by timing noise (TN), and we present a new method for characterizing the noise process and mitigating its effects on other facets of the timing model. We present an analysis of TN over the population using a new metric for characterizing its strength and spectral shape, namely, its time-domain correlation. The dependence of the strength ν and n is in good agreement with previous studies. We find that noise process power spectra S(f) for unrecycled pulsars are steep, with strong correlations over our entire data set and spectral indices S(f) α f- α of a ~ 5-9. One possible explanation for these results is the occurrence of unmodeled, episodic "microglitches." Finally, we show that our treatment of TN results in robust parameter estimation, and in particular we measure a precise timing position for each pulsar. We extensively validate our results with multi-wavelength astrometry, and using our updated position, we firmly identify the X-ray counterpart of PSR J1418-6058.